From the Borders: Uncovering Implicit Definitions of Whiteness From the Perspective of the Questionably White - Cohen, Nathalie (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1997)
Many scholars believe that locating Whiteness as a racialized ethnicity and examining how Whiteness constructs race and racism is crucial to the work of anti-racist feminism. Not often considered, but of equal significance, are folk taxonomies of Whiteness, implicit and unstated concepts and definitions employed every day in our society, and in scholarly anti-racist Works. As it is often from the borders that one can more clearly see and critique the centre, it is from an analysis of my own and other women’s experiences of Questionable-Whiteness, the racially uncertain location between Whiteness and Otherness, that I examine the different modes of defining Whiteness and race, as well as their links with class, religion, and national identity.